Ethnozoology in the mountains. What does the cognitive salience of wild animals tell us? - Wajner, Matias (2019)
In recent times, ethnobiology has revived interest in cognitive aspects of humans' communities. A concept commonly used in this area is cognitive salience. In this paper we assess the wild animal salience meaning for the rural people from an area of the mountain range of the Cordoba province (Argentina). We also analyzed the relationship of cultural and ecological factors over wild animal domain salience. The values of cognitive salience, perception and cultural value were obtained by means of free lists to 16 collaborators, while semistructured interviews were used to inquire about local ecological knowledge and ease of observation about wild animals. The interdependence between the five variables elaborated was analyzed through a Principal Components Regression. The results show a qualitative relationship between Cognitive Salience and Cultural Value and a significant correlation between Cognitive Salience and Local Ecological Knowledge. Ease of Observation did not correlate with Cognitive Salience, but show a significant relationship with the Perceived Abundance. The results suggest a complex network of factors that are modeling the cognitive salience and local perceptions over wild animals. In our findings, highlight the Cultural Value given to harmful animals which reflects an increasing pattern in the region, the conflict between rural people and wild animals. In turn a mutual influences and causal feedback loops between cognitive salience and an ecological factor, the Perceived abundance, is proposed. Investigations over cognition and about how people perceived nature can give us an idea of how they act in it, a compelling factor when it comes to cultural and biological conservation issues.